MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KARAKTER WASAKA PADA MUATAN IPAS MENGGUNAKAN MODEL PBL, NHT DAN MAKE A MATCH TERINTEGRASI STEAM PADA SISWA SEKOLAH DASAR - Rahayu; Annisa , Muhsinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the lack of critical thinking skills in the IPAS subject and the low value of the WASAKA (hard work) character during the learning process. The solution to this problem is the use of a combination of Problem Based Learning, Numbered Heads Together, and Make A Match models integrated with the STEAM approach. This study aims to analyze students’ critical thinking skills and WASAKA character through Classroom Action Research (CAR) conducted in two cycles. The subjects of this study were 25 fourth-grade elementary school students. The results showed that students' critical thinking skills reached 96% with a very critical category, and the WASAKA character reached 100% with a deeply embedded category.